Herpes Zoster: A Rare Dermatosis in Childhood (About 25 Cases) - Fatimazahra El Fatoiki; Yousra Habibi; Anas Saddik; Fouzia Hali; Soumya Chiheb (Journal of Tropical Medicine)
Conclusion: Herpes zoster is a rare condition in children, typically evolving without sequelae.